Particle mixing in liquid fluidised beds - Hassan, Onn (1997)
Rapid particle mixing in fluidised beds is one of the major advantages in their application. Much work has been done on the measurement and correlation of heat transfer coefficients with the basic physical properties of the system; however, their dependence on the fluid and solids flow patterns is not fully understood. In this investigation, a mathematical model was employed to predict the unsteady thermal behaviour of the liquid fluidised systems. The bed was considered as being divided into a series of cells, each containing a homogenised mixture of liquid and particles. Hence, the level of mixing decreased with increasing number of cells. The predicted thermal responses in the liquid stream emerging from the surface of the bed were compared with those measured in the experiments. Thus the degree of particle mixing inside fluidized beds can be determined.